2017
DOI: 10.1016/j.jspr.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of particle size, food contamination, and residual efficacy of pyrethrin + methoprene aerosol

Abstract: Efficacy of aerosol applications of pyrethrin+methoprene was assessed through emergence of morphologically-normal adults exposed as larvae and through a developmental index. Concrete arenas were treated with aerosol droplets (particles) averaging 2µm or 16µm, food material was placed on the arenas at 1-8 weeks post-treatment, and 3-4-week-old larvae of one of four stored product insect species placed on the arenas at the same time. No exposed Lasioderma serricorne (DeGeer) larvae reached the adult stage at eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
4
14
1
Order By: Relevance
“…Eight out of the 20 locations had complete adult recovery after a week. The ability of affected adult T. confusum to recover as observed in this study is consistent with previous research [5,6,8,10]. The affected state, or knockdown as it is sometimes termed, is a transitional category from which individual insects may survive or die, with the outcome likely related to the dosage of insecticide received [8].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Eight out of the 20 locations had complete adult recovery after a week. The ability of affected adult T. confusum to recover as observed in this study is consistent with previous research [5,6,8,10]. The affected state, or knockdown as it is sometimes termed, is a transitional category from which individual insects may survive or die, with the outcome likely related to the dosage of insecticide received [8].…”
Section: Resultssupporting
confidence: 89%
“…Aerosol particle size is a critical factor affecting the efficacy of insecticides, since smaller droplets tend not to settle onto surfaces or impinge on the insect cuticle. For example, laboratory testing in a continuous flow chamber has demonstrated how larger particle sizes of 16 µm were more effective than smaller particle sizes of 2 µm at preventing Tribolium confusum Jacquelin du Val, confused flour beetle, and Trogoderma variabile Ballion, warehouse beetle, development from the larval to the adult stage [6]. Particle size also impacts movement of particles within a structure, with larger droplets traveling shorter distances than smaller droplets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data show a temporary effect in adult movement, which may be desirable, as the inclusion of a neurotoxic agent along with methoprene slows down the exposed adults without terminating the exposure. As methoprene acts on the immatures, the inclusion of an adulticide, such as deltamethrin, is expected to cause adult mortality [24][25][26][27]. For instance, Athanassiou et al [28] used a combination of methoprene with natural pyrethrum, and found that all the exposed psocid individuals were dead in a very short interval, an effect that was apparently due to the presence of natural pyrethrum and not to methoprene.…”
Section: Discussionmentioning
confidence: 99%
“…Due to damage caused by these insects, the difficulty of controlling them, and because many species, such as L. serricorne, have already acquired resistance to insecticides [5], new alternatives aimed at minimizing economic losses and controlling pests efficiently become necessary, as is the case of biological control with the use of parasitoids [6].…”
Section: Introductionmentioning
confidence: 99%